Hungarian Monitoring, 26 June 1989 . [Magyar rádiófigyelő], 1989. június 26 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Transcripts of Hungarian national radio programs produced by the Hungarian Monitoring Unit of Radio Free Europe/Radio Liberty. A magyar országos rádióadók műsorainak a Szabad Európa Rádió/Szabadság Rádió Magyar Monitoring Osztálya által készített átiratai. International Politics: - Czechoslovak, Polish and East German opinions on Hungarian Socialist Workers' Party (MSZMP) Central Committee decisions - Workers' protests in Romania against developments in Hungary - Foreign and western reactions to the Central Committee session - Wide-ranging reprisals! Campaign in China - On the Soviet supreme council sitting Domestic Affairs: - Hungarian Socialist Workers' Party (MSZMP) four-member presidium holds international press conference - Many criticize Károly Grósz at Budapest Party committee - Csaba Tabajdi's acquittal - Ministerial council in session: personnel changes, directive concerning situation of those interned before 1953, passport law, World Exposition - Foreign minister Gyula Horn meets Chancellor Vranitzkya and foreign minister Mock in Vienna for talks, takes part in press conference - Wire fence along Hungarian-Romanian border dismantled on Romanian side - Daughter of Romanian opposition teacher D. Cornea makes statement in Budapest in connection with Romanian accusations relating to funeral of Imre Nagy - Leading Hungarian intellectuals set up European Forum in Budapest Külpolitika: - Csehszlovák, lengyel és NDK vélemények az MSZMP KB ülésének határozatairól - Tiltakozó munkásgyűlések Romániában a magyar fejlemények miatt - Külföldi - Nyugati visszhangok a KB ülésről - Széleskörű megtorlás! kampány Kínában - A szovjet legfelső tanács üléséről Belpolitika: - Az MSZMP négytagú elnöksége nemzetközi sajtóértekezletet tartott - Sokan bírálták Grósz Károlyt a budapesti pártbizottságban - Tabajdi Csaba felmentése - Ülést tartott a Minisztertanács: személyi változások, rendelet az 1953 előtt internáltak helyzetéről, útlevél törvény, világkiállítás - Horn Gyula külügyminiszter Bécsben Vranitzky kancellárral és Mock külügyminiszterrel tárgyalt és sajtóértekezleten vett részt - Bontják a drótkerítést a magyar-román határ román oldalán - D. Cornea román ellenzéki tanárnő lányának nyilatkozata a Nagy Imre temetésével kapcsolatos román vádakról - Megalakul az Európa Fórum